Finger injuries in international judo competitions - Yamamoto, Y.; Kamiya, N.; Anai, T.; Tokuda, S.; Hosokawa, S. (The Arts and Sciences of Judo, 2025)
The purpose of this study was to investigate and examine the actual situation of hand injuries, including finger and fingernail injuries, which are currently of concern to the International Judo Federation (IJF), and to contribute to the revision of regulations, if necessary, for the development of judo. The results showed that the overall incidence of injuries on hands and fingers, including fingernails, was 0.99% of contests in international competitions (i.e. 27 injuries in 2,716 contests from world judo championships in 2021, 22, 23, and 24), which is much higher than judo`s common injuries (i.e. knee, shoulder, elbow, head). In 22 cases (82%), injuries occurred when the hand holding the judo suit was separated or pulled apart suddenly and forcibly from tsurite (i.e. collar hand) or hikite (i.e. sleeve hand). In terms of kumite, 17 cases (63%) of the contests were ai-yotsu kumite (i.e. the same kumite as the opponent) and 10 cases (37%) were kenka-yotsu kumite (i.e. opposite kumite to the opponent). The middle finger appeared to be more injured than the other fingers. The incidence of hand/finger injuries varies in the literature, however, the current study postulates that hand/finger injuries are one of the most common injuries in judo at present, which could be reduced under the control of the IJF by changing judo rules and suits in the future.